Modified Cam-clay Model Parameters M of Kunming Red Clay. (1st March 2023) - Liu, Xianru; Li, Jianguang; Yi, Ren; Zhao, Kuangjie
Abstract: Red clay is widely distributed in Kunming. At present, there are many engineering projects in Kunming, and many engineering projects are built on red clay. Therefore, it is very important to study the mechanical properties of red clay. Kunming red clay was remolded and prepared, and triaxial consolidation drainage tests of remolded saturated clay with the same water content and different dry densities were designed. Through the triaxial consolidation drainage test, the shear strength parameters of Kunming saturated red clay and the modified Cam-clay model parameters are obtained. The experimental results show that the modified Cam-clay model parameters of saturated red clay with the same water content and dry density are basically equal, and the larger the dry density is, the larger the modified Cam-clay model parameter M of saturated red clay is. The test results can provide reference data for engineering design in the Kunming area and modified Cam-clay model simulation in the Kunming area.